2005
DOI: 10.1007/s00213-005-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Timing of nicotine effects on learning in zebrafish

Abstract: This position discrimination procedure in zebrafish effectively demonstrated the cognitive-enhancing effects of nicotine. This model may be useful in the early screening of novel nicotinic compounds for treatment of cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 32 publications
2
77
1
1
Order By: Relevance
“…At present, the mechanism(s) by which atropine appears to potentiate the effects of donepezil is unclear; effects at pre-and postjunctional muscarinic receptors could be explored with the use of selective antagonists. Overall, the results obtained with donepezil in zebrafish larvae support an effect on habituation behavior via nicotinic receptors, which is in keeping with previous findings demonstrating a cognitive enhancing effect of nicotine in adult zebrafish (Levin et al, 2006a).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…At present, the mechanism(s) by which atropine appears to potentiate the effects of donepezil is unclear; effects at pre-and postjunctional muscarinic receptors could be explored with the use of selective antagonists. Overall, the results obtained with donepezil in zebrafish larvae support an effect on habituation behavior via nicotinic receptors, which is in keeping with previous findings demonstrating a cognitive enhancing effect of nicotine in adult zebrafish (Levin et al, 2006a).…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies in zebrafish and mammals have demonstrated learning effect through the nicotinic (Levin and Simon, 1998;Power et al, 2003;Levin et al, 2006a) and muscarinic (Levin and Simon, 1998;Power et al, 2003;Levin et al, 2006a) cholinergic receptors. Levin and Chen (2004) and Levin et al (2006b) have studied extensively the effects of nicotine on learning and memory in zebrafish and have shown that low doses of nicotine enhance memory while higher doses impair memory in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dlugos and Rabin (Dlugos and Rabin, 2003) and Gerlai et al (Gerlai et al, 2006) have also demonstrated adaptation of adult zebrafish after chronic exposure to ethanol such that tolerance to the acute effects of the drug develops. By contrast, studies of the effect of nicotine on zebrafish development and behaviour are limited (Levin et al, 2007;Levin and Chen, 2004;Levin et al, 2006;Matta et al, 2007;Svoboda et al, 2002). Levin et al have shown that 3·min exposure to low doses of nicotine (38-77·mol·l -1 nicotine) improves memory function in zebrafish (Levin and Chen, 2004) and that acute exposure to similar concentrations has an anxiolytic effect (Levin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, little study has been conducted regarding the muscarinic cholinergic system, either in adult or larval zebrafish, though nicotinic receptor agonists improve spatial discrimination learning in zebrafish, which is blocked by nicotinic antagonists (Levin et al, 2006). In this study, it is hypothesized, based on the presence of choline acetyltransferase (ChAT), an acetylcholine-synthesizing enzyme, and AChE, an acetylcholine-degrading enzyme in the zebrafish brain, that the muscarinic cholinergic system plays a role in learning and memory of passive avoidance response in zebrafish.…”
Section: Introductionmentioning
confidence: 99%